The Study of Seepage Coefficient on Tertiary Irrigation Canals in The Sei Beras Sekata Village, Irrigation Area Medan Krio, Sunggal District of Deli Serdang - Ika Sundari; Sumono Sumono; Achwil Putra Munir (Universitas Sumatera Utara, 2014)
In distribution of irrigation water through tertiary canal which is land canal, water losses can occur through evapotranspiration, percolation, and seepage of the canal, there by effecting the efficiency of water distribution. From the third factors of water losses the seepage coefficient is more difficult to determine. This research was aimed to study the value of the seepage coefficient using empirical formulas in two tertiary canals in Sei Beras Sekata village Medan Krio irrigation area, Sunggal district of Deli Serdang. The results showed that seepage coefficient in the right edge of the first canal was 8899,2 mm/day, at the left edge was 26697,6 mm/day; at the right edge of second canal was 78796,8 mm/day and at the left edge was 23241,6 mm/day. Efficiency on first that canal and second canal were 73,93% and 71,03% respectively. Key Word: Seepage coefficient,tertiary canal, water conveyance efficiency, water loss